Phenotype Switching in Chemotaxis Aggregation Models Controls the Spontaneous Emergence of Large Densities - Painter, Kevin J.; Winkler, Michael (SIAM Journal on Applied Mathematics)
Keywords: Applied Mathematics

Avoiding critical mass phenomena by arbitrarily mild saturation of cross-diffusive fluxes in two-dimensional Keller-Segel-Navier-Stokes systems - Winkler, Michael; Yokota, Tomomi (Journal of Differential Equations)
Keywords: Analysis; Applied Mathematics

Absence of collapse into persistent Dirac-type singularities in a Keller-Segel-Navier-Stokes system involving local sensing - Winkler, Michael (Advances in Differential Equations)
Keywords: Applied Mathematics; Analysis

A Viewpoint on Human Factors in Software Supply Chain Security: A Research Agenda - Fourné, Marcel; Wermke, Dominik; Fahl, Sascha; Acar, Yasemin (IEEE Secur. Priv.)

Turnover-Based Corporate Income Taxation and Corporate Risk-Taking - Amberger, Harald; Siahaan, Fernando; Sureth-Sloane, Caren

"We’ve Disabled MFA for You": An Evaluation of the Security and Usability of Multi-Factor Authentication Recovery Deployments - Amft, Sabrina; Höltervennhoff, Sandra; Huaman, Nicolas; Krause, Alexander; Simko, Lucy; Acar, Yasemin; Fahl, Sascha (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security, CCS 2023, Copenhagen, Denmark, November 26-30, 2023)

Security, Privacy, and Data-sharing Trade-offs When Moving to the United States: Insights from a Qualitative Study - Tran, Mindy; Munyendo, Collins W; Sri Ramulu, Harshini; Rodriguez, Rachel Gonzalez; Schnell, Luisa Ball; Sula, Cora; Simko, Lucy; Acar, Yasemin (2024 IEEE Symposium on Security and Privacy (SP))

"We’ve Disabled MFA for You": An Evaluation of the Security and Usability of Multi-Factor Authentication Recovery Deployments - Amft, Sabrina; Höltervennhoff, Sandra; Huaman, Nicolas; Krause, Alexander; Simko, Lucy; Acar, Yasemin; Fahl, Sascha (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security)

A Viewpoint on Human Factors in Software Supply Chain Security: A Research Agenda - Fourné, Marcel; Wermke, Dominik; Fahl, Sascha; Acar, Yasemin (IEEE Security & Privacy)

The Use and Non-Use of Technology During Hurricanes - Simko, Lucy; Sri Ramulu, Harshini; Kohno, Tadayoshi; Acar, Yasemin (Proc. ACM Hum. Comput. Interact.)

"Oh yes! over-preparing for meetings is my jam :)": The Gendered Experiences of System Administrators - Kaur, Mannat; Sri Ramulu, Harshini; Acar, Yasemin; Fiebig, Tobias (Proc. ACM Hum. Comput. Interact.)

Neue Wege im mathematischen Unterricht: Auf den Spuren Mathilde Vaertings - Werth, Gerda

Standardkonstruktionen eigenständig entdecken. Mathilde Vaertings Idee der Selbstständigkeitsprobe - Werth, Gerda (mathematik lehren)

Bruchmechanische Untersuchung des Dualphasenstahls HCT590X unter Temperatureinfluss - Weiß, Deborah; Duffe, Tobias; Buczek, Moritz; Kullmer, Gunter; Schramm, Britta

CLIL - Content and Language Integrated Learning - Böttger, Lydia; Niederhaus, Constanze (Berufs- und Fachsprache Deutsch in Wissenschaft und Praxis. Ein Handbuch aus DaF- und DaZ Perspektive)

$L^2$-spectrum, growth indicator function and critical exponent on locally symmetric spaces - Wolf, Lasse L.; Zhang, Hong-Wei (arXiv:2311.11770)
In this short note we observe, on locally symmetric spaces of higher rank, a connection between the growth indicator function introduced by Quint and the modified critical exponent of the Poincar\'e series equipped with the polyhedral distance. As a consequence, we provide a different characterization of the bottom of the $L^2$-spectrum of the Laplace-Beltrami operator in terms of the growth indicator function. Moreover, we explore the relationship between these three objects and the temperedness.

Design-Based Research als Erforschung und Gestaltung von Interaktionsprozessen zwischen Wissenschaft und Bildungspraxis - Jenert, Tobias (Wissenschaft trifft Praxis – Designbasierte Forschung in der beruflichen Bildung)
Das Verhältnis zwischen Wissenschaft und Praxis wurde in unterschiedlichen Forschungsansätzen im- mer wieder wissenschaftlich betrachtet. Dennoch ist es notwendig, sich im Rahmen der wissenschafts- theoretischen Konzeption von Design-Based Research (DBR) weiter damit auseinanderzusetzen, denn Interaktion zwischen Wissenschaft und Bildungspraxis ist ein zentrales Merkmal von DBR. Dieser Beitrag befasst sich mit der Frage, wie sich diese Interaktion je nach zugrunde liegendem DBR-Verständnis me- thodologisch fassen lässt. Die Interaktion wird als ein wesentlicher Bestandteil des Erkenntnisprozesses in DBR aufgefasst. Daher wird neben der methodischen Ausgestaltung von Interaktionsprozessen auch methodologisch reflektiert, was die Wissenschaft-Praxis-Interaktion für die Erkenntnis an sich bedeutet.

JuGaze: A Cell-based Eye Tracking and Logging Tool for Jupyter Notebooks - Sparmann, Sören; Hüsing, Sven; Schulte, Carsten (Proceedings of the 23rd Koli Calling International Conference on Computing Education Research)

Resonances and Weighted Zeta Functions for Obstacle Scattering via Smooth Models - Delarue, Benjamin; Schütte, Philipp; Weich, Tobias (Annales Henri Poincaré)
Abstract We consider a geodesic billiard system consisting of a complete Riemannian manifold and an obstacle submanifold with boundary at which the trajectories of the geodesic flow experience specular reflections. We show that if the geodesic billiard system is hyperbolic on its trapped set and the latter is compact and non-grazing, the techniques for open hyperbolic systems developed by Dyatlov and Guillarmou (Ann Henri Poincaré 17(11):3089–3146, 2016) can be applied to a smooth model for the discontinuous flow defined by the non-grazing billiard trajectories. This allows us to obtain a meromorphic resolvent for the generator of the billiard flow. As an application we prove a meromorphic continuation of weighted zeta functions together with explicit residue formulae. In particular, our results apply to scattering by convex obstacles in the Euclidean plane.
Keywords: Mathematical Physics; Nuclear and High Energy Physics; Statistical and Nonlinear Physics

Singular cohomology of symplectic quotients by circle actions and Kirwan surjectivity - Delarue, Benjamin; Ramacher, Pablo; Schmitt, Maximilian (arXiv:2312.03634)
Let $M$ be a symplectic manifold carrying a Hamiltonian $S^1$-action with momentum map $J:M → \mathbb{R}$ and consider the corresponding symplectic quotient $\mathcal{M}_0:=J^{-1}(0)/S^1$. We extend Sjamaar's complex of differential forms on $\mathcal{M}_0$, whose cohomology is isomorphic to the singular cohomology $H(\mathcal{M}_0;\mathbb{R})$ of $\mathcal{M}_0$ with real coefficients, to a complex of differential forms on $\mathcal{M}_0$ associated with a partial desingularization $\widetilde{\mathcal{M}}_0$, which we call resolution differential forms. The cohomology of that complex turns out to be isomorphic to the de Rham cohomology $H(\widetilde{ \mathcal{M}}_0)$ of $\widetilde{\mathcal{M}}_0$. Based on this, we derive a long exact sequence involving both $H(\mathcal{M}_0;\mathbb{R})$ and $H(\widetilde{ \mathcal{M}}_0)$ and give conditions for its splitting. We then define a Kirwan map $\mathcal{K}:H_{S^1}(M) → H(\widetilde{\mathcal{M}}_0)$ from the equivariant cohomology $H_{S^1}(M)$ of $M$ to $H(\widetilde{\mathcal{M}}_0)$ and show that its image contains the image of $H(\mathcal{M}_0;\mathbb{R})$ in $H(\widetilde{\mathcal{M}}_0)$ under the natural inclusion. Combining both results in the case that all fixed point components of $M$ have vanishing odd cohomology we obtain a surjection $\check κ:H^ev_{S^1}(M) → H^ev(\mathcal{M}_0;\mathbb{R})$ in even degrees, while already simple examples show that a similar surjection in odd degrees does not exist in general. As an interesting class of examples we study abelian polygon spaces.

A Riemann-Roch formula for singular reductions by circle actions - Delarue, Benjamin; Ioos, Louis; Ramacher, Pablo (arXiv:2302.09894)
We compute a Riemann-Roch formula for the invariant Riemann-Roch number of a quantizable Hamiltonian $S^1$-manifold $(M,ω,\mathcal{J})$ in terms of the geometry of its symplectic quotient, allowing $0$ to be a singular value of the moment map $\mathcal{J}:M→\mathbb{R}$. The formula involves a new explicit local invariant of the singularities. Our approach relies on a complete singular stationary phase expansion of the associated Witten integral.

Investigations of Ni-based methanation catalysts under dynamic conditions via hard X-ray spectroscopy - Strübbe, Sven
Im Rahmen dieser Dissertation wurden Katalysatoren, welche auf der thermischen Zersetzung von metallorganischen Gerüstverbindungen basieren, mittels Röntgenabsorptionsspektroskopie (XAS) und Röntgenemissionsspektroskopie (XES) untersucht. Durch diesen synthetischen Ansatz können hochdisperse Ni-basierte Katalysatoren eingebettet in einer Kohlenstoffmatrix gewonnen werden, welche für die Methanisierung von CO2 Einsatz finden. Diese sollen eine hohe Stabilität gegenüber Wasserstoffausfällen aufweisen, welche bedingt durch Wetterfluktuationen in der Gewinnung von grünem Wasserstoff auftreten. Um ein derartiges System gezielt gestalten zu können, ist ein detailliertes Verständnis zugrundeliegender chemischer Mechanismen und damit einhergehend elektronischer Strukturen der Katalysatorsysteme notwendig. Durch die detaillierte Analyse der Katalysator-Vorstufen mittels XAS konnte gezeigt werden, dass auch unter reduktiven Bedingungen in der thermischen Zersetzung Spuren von Ni(II) vorliegen und keine reine Nifcc-Struktur erreicht werden konnte. Eine detaillierte Auswertung der gleichen Präkatalysatoren mittels XES konnte durch eine neuartige Kombination von HERFD-XANES, theoretischer Berechnungen und VtC-XES einen eindeutigen Beweis für das Vorhandensein der gewünschten Kohlenstoffmatrix sowie Spuren von NiO im Präkatalysator liefern, welche sich vorteilhaft auf die spätere Aktivität im finalen Katalysator auswirken. Abschließend konnte mittels einer in-situ Untersuchung der Temperaturbereich, in dem sich die aktive Katalysatorspezies ausbildet, auf 80 bis 200 C eingegrenzt werden. Schließlich konnte ein eindeutiger Zusammenhang zwischen dem Verlust einer stabilisierenden Kohlenstoffschicht und einem Rückgang der Aktivität belegt werden.

Das Projekt "Schule für Alle" der Universität Bielefeld: ein Mentoring-Projekt mit rassismuskritischen Ansätzen in Deutschland - Pieper, Catania; Kottmann, Brigitte; Reh, Anne (Mentoring-Projekt für Roma-Kinder in Europa)

Demo: Chat based Emergency Service via Long Range Wireless Communication (LoRa) - Stiballe, Alisa; Welzel, Simon; Dorfschmidt, Johannes; Schluter, Darvin; Steuter, Dominik Delgado; Hense, Jannik Lukas; Klingler, Florian (2023 IEEE 48th Conference on Local Computer Networks (LCN))

Low Earth Orbit Satellite Supported Multi-Hop Dissemination of Messages in V2X Networks - Franke, Mario; Stroop, Roland; Klingler, Florian; Sommer, Christoph (2023 IEEE 97th Vehicular Technology Conference (VTC2023-Spring))

Ingo Schulze und Frank Witzel im Dialog. Die 40. Paderborner Gastdozentur für Schriftsteller und Schriftstellerinnen und das sie begleitende wissenschaftliche Symposium. In: Werke im Dialog. (Virtuelle) Begegnungen in 40 Jahren „Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller“ - Eke, Norbert Otto; Elit, Stefan (Zeitschrift für deutsche Philologie)

Virtuelle Begegnungen. Nach vier Jahrzehnten Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller. In: Werke im Dialog. (Virtuelle) Begegnungen in 40 Jahren „Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller“ - Eke, Norbert Otto; Elit, Stefan (Zeitschrift für deutsche Philologie)

Geleitwort. In: Werke im Dialog. (Virtuelle) Begegnungen in 40 Jahren „Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller“ - Eke, Norbert; Elit, Stefan (Zeitschrift für deutsche Philologie)

Werke im Dialog. (Virtuelle) Begegnungen in 40 Jahren „Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller“ (Zeitschrift für deutsche Philologie)

Handbuch Versepik

[Klopstocks] Sprachtheoretische Schriften - Elit, Stefan (Klopstock-Handbuch. Leben – Werk – Wirkung)

[Klopstocks] Liebe und Freundschaft - Elit, Stefan (Klopstock-Handbuch. Leben – Werk – Wirkung)

Coupled CP Tensor Decomposition with Shared and Distinct Components for Multi-Task Fmri Data Fusion - Borsoi, R. A.; Lehmann, Isabell; Akhonda, M. A. B. S.; Calhoun, V. D.; Usevich, K.; Brie, D.; Adali, T. (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Deriving 3D Functional Brain Regions from Multi-Slice Functional Ultrasound Data Using ICA and IVA - Lehmann, Isabell; Adali, Tülay; Kruizinga, Pieter; Hunyadi, Borbála (2023 57th Asilomar Conference on Signals, Systems, and Computers)

Einleitung - Elit, Stefan; Bremer, Kai (Handbuch Versepik)

‚[M]uch too terrible for representation‘. Musik und Geräusch in Matthew Lewis’ Melodram The Captive (1803) - Ricke, Anna (Musik und das Unheimliche)

Flexibilitätsgeprägte Biographien als methodische Herausforderung – Das Beispiel der Musikerin Smaragda Eger-Berg - Ricke, Anna (Kulturelles Handeln | Macht | Mobil. Interdisziplinäre Studien zur gender- und musikbezogenen Mobilitätsforschung)

Musikwelten der Wiener Moderne. Das Beispiel der künstlerischen Emanzipation der Musikerin Smaragda Eger-Berg - Ricke, Anna (It's a Man's World? Künstlerinnen in Europas Musik-Metropolen des frühen 20. Jahrhunderts)

An interval multi-criteria decision-making model for evaluating blockchain-IoT technology in supply chain networks - Tavana, Madjid; Khalili Nasr, Arash; Ahmadabadi, Alireza Barati; Amiri, Alireza Shamekhi; Mina, Hassan (Internet of Things)
Keywords: Management of Technology and Innovation; Artificial Intelligence; Computer Science Applications; Hardware and Architecture; Engineering (miscellaneous); Information Systems; Computer Science (miscellaneous); Software

Analytic hierarchy process and data envelopment analysis: A match made in heaven - Tavana, Madjid; Soltanifar, Mehdi; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

A bi-objective hybrid vibration damping optimization model for synchronous flow shop scheduling problems - Tavana, Madjid; Hajipour, Vahid; Alaghebandha, Mohammad; Di Caprio, Debora (Machine Learning with Applications)
Keywords: General Medicine

A general Best-Worst method considering interdependency with application to innovation and technology assessment at NASA - Tavana, Madjid; Mina, Hassan; Santos-Arteaga, Francisco J. (Journal of Business Research)
Keywords: Marketing

Analytical hierarchy process: revolution and evolution - Tavana, Madjid; Soltanifar, Mehdi; Santos-Arteaga, Francisco J. (Annals of Operations Research)
Keywords: Management Science and Operations Research; General Decision Sciences

A fuzzy preference programming and weighted influence non-linear gauge system for mission architecture assessment at NASA - Tavana, Madjid; Heidary, Mohammad Saeed; Mina, Hassan (Applied Soft Computing)
Keywords: Software

A Credibility and Strategic Behavior Approach in Hesitant Multiple Criteria Decision-Making With Application to Sustainable Transportation - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid; Tena, Emilio Cerda (IEEE Transactions on Fuzzy Systems)
Keywords: Applied Mathematics; Artificial Intelligence; Computational Theory and Mathematics; Control and Systems Engineering

Value Chain digitalization and technological development as innovation catalysts in small and medium-sized enterprises - Marín, Raquel; Santos-Arteaga, Francisco J.; Tavana, Madjid; Di Caprio, Debora (Journal of Innovation & Knowledge)
Keywords: Management of Technology and Innovation; Marketing; Economics and Econometrics; Business and International Management

An integrated decision support framework for resilient vaccine supply chain network design - Tirkolaee, Erfan Babaee; Torkayesh, Ali Ebadi; Tavana, Madjid; Goli, Alireza; Simic, Vladimir; Ding, Weiping (Engineering Applications of Artificial Intelligence)
Keywords: Electrical and Electronic Engineering; Artificial Intelligence; Control and Systems Engineering

A hybrid multi-attribute decision-making and data envelopment analysis model with heterogeneous attributes: The case of sustainable development goals - Soltanifar, Mehdi; Tavana, Madjid; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Environmental Science & Policy)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Spacecraft tracking control and synchronization: An assessment of conventional, unconventional, and combined methods - Deveci, Muhammet; Pamucar, Dragan; Gokasar, Ilgin; Tavana, Madjid (Advances in Space Research)
Keywords: Space and Planetary Science; Aerospace Engineering; General Earth and Planetary Sciences; Atmospheric Science; Geophysics; Astronomy and Astrophysics

A novel median-based optimization model for eco-efficiency assessment in data envelopment analysis - Dellnitz, Andreas; Tavana, Madjid; Banker, Rajiv (Annals of Operations Research)
Keywords: Management Science and Operations Research; General Decision Sciences